2011
DOI: 10.1371/journal.pone.0018479
|View full text |Cite
|
Sign up to set email alerts
|

What the Public Was Saying about the H1N1 Vaccine: Perceptions and Issues Discussed in On-Line Comments during the 2009 H1N1 Pandemic

Abstract: During the 2009 H1N1 pandemic, a vaccine was made available to all Canadians. Despite efforts to promote vaccination, the public's intent to vaccinate remained low. In order to better understand the public's resistance to getting vaccinated, this study addressed factors that influenced the public's decision making about uptake. To do this, we used a relatively novel source of qualitative data – comments posted on-line in response to news articles on a particular topic. This study analysed 1,796 comments posted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 28 publications
7
115
0
Order By: Relevance
“…This openness is most likely an effect of participants posting anonymously, which apparently permitted them to express their thoughts and feelings with a freedom they may not find in interviews, focus groups, or questionnaires (Porter & Ispa, 2012;Wilkinson & Thelwall, 2011). Similar to Henrich and Holmes (2011) who concluded that social media discussions can be seen as reliable sources of data, this study found a high degree of corroboration between the social media discussions and the findings of research using interviews and focus groups.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…This openness is most likely an effect of participants posting anonymously, which apparently permitted them to express their thoughts and feelings with a freedom they may not find in interviews, focus groups, or questionnaires (Porter & Ispa, 2012;Wilkinson & Thelwall, 2011). Similar to Henrich and Holmes (2011) who concluded that social media discussions can be seen as reliable sources of data, this study found a high degree of corroboration between the social media discussions and the findings of research using interviews and focus groups.…”
Section: Resultssupporting
confidence: 74%
“…Unlike traditional print news articles, online news articles feature interactivity through a comments section that allows readers to post comments at the end of the article, and this feature has been found to allow for diverse opinions (Manosevitch & Walker, 2009). By examining the discussions posted in response to news articles on the H1N1 vaccine, Henrich and Holmes (2011) discovered that the online themes were consistent with the findings from surveys and focus groups, and the authors conclude that online discussions provide reliable sources of data. Yet, in spite of such advantages, teachers' social media discussions have remained an understudied area of education research (Stitzlein & Quinn, 2012).…”
Section: Alternative Data Sources For Understanding Teachers' Perspecmentioning
confidence: 65%
See 1 more Smart Citation
“…Henrich & Holmes (2011) provide a useful way of thinking about how to analyse any online data [16]: They were interested in developing a set of themes that would let them see public perceptions of the H1N1 vaccine and assumed that the more a topic is mentioned, the more powerful it is in influencing vaccination decision. They looked at 1796 online comments and found the following themes: fear of H1N1 (low and highincluding reasons), responsibility of media, government competency, government trustworthiness, fear of vaccine, pharmaceutical companies and personal protective measures.…”
Section: Themes and Contentmentioning
confidence: 99%
“…61,62,79,95 (3) Low levels of awareness did not seem to contribute to low H1N1vaccine uptake. 89 It appears that media coverage 90 and efforts of the official agencies were effective in promoting understanding and knowledge.…”
Section: Vaccination Of Males Against Human Papilloma Virus: Acceptanmentioning
confidence: 99%